PENGEMBANGAN PEMBELAJARAN BERBASISWEB DAN INTERNET - Umar, Sofyan; Muhammad Yaumi; Muh. Yusuf T (IAI DDI POLEWALI MANDAR, 2024)
Knowledge and learning are interconnected, where learning is necessary to acquire knowledge. The development of Information and Communication Technology (ICT) has influenced various aspects of life, including education. The role of ICT in learning includes methods such as blended learning, hybrid learning, computer-based learning, and web-based learning. Web-based learning media enables global access, the use of multimedia, interactivity, customization, rapid updates, measurement and evaluation, accessibility, security, collaboration, monitoring, and feedback. Web-based learning creates a virtual learning environment with various facilities such as discussion forums, chat, online assessments, and administrative systems.